2018
DOI: 10.1103/physrevapplied.9.024027
|View full text |Cite
|
Sign up to set email alerts
|

Midinfrared Surface Plasmons in Carbon Nanotube Plasmonic Metasurface

Abstract: We report an experimental observation of the midinfrared surface plasmon excited in a carbon nanotube plasmonic metasurface. The absorption of a 400-nm-thick single-walled carbon nanotube film perforated with laser-drilled subwavelength holes arranged in a 2D lattice is resonantly enhanced by 75% as compared with the unstructured film. The enhancement of absorption has a resonant behavior associated with the excitation of the surface plasmon and occurs at the wavelengths around 15 μm for the lattice period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Single-walled carbon nanotube (SWCNT) films have been proven to be prospective candidates for numerous applications in many fields of science and technology. Among the most promising examples of SWCNT implementations are transparent electrodes, 1,2 smart textiles, 3,4 ultrasensitive photodetectors, 5,6 highly-efficient solar cells, 7,8 light-emitting diodes, 9,10 and ultrafast lasers for near and midinfrared wavelength ranges. 11,12 All these applications, as well as almost any task related to the development of devices based on SWCNT films, strongly require a rapid, versatile, and preferably contactless method to determine the film thicknesses and their optical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Single-walled carbon nanotube (SWCNT) films have been proven to be prospective candidates for numerous applications in many fields of science and technology. Among the most promising examples of SWCNT implementations are transparent electrodes, 1,2 smart textiles, 3,4 ultrasensitive photodetectors, 5,6 highly-efficient solar cells, 7,8 light-emitting diodes, 9,10 and ultrafast lasers for near and midinfrared wavelength ranges. 11,12 All these applications, as well as almost any task related to the development of devices based on SWCNT films, strongly require a rapid, versatile, and preferably contactless method to determine the film thicknesses and their optical properties.…”
mentioning
confidence: 99%
“…However, it does not guarantee good reliable results, as was shown by Barnes et al, where an agreement with an experimental absorption spectrum was demonstrated only within 20%. 15 Besides, the AFM methods are not applicable in the case of freestanding films used in ultrasensitive photodetectors, 5 efficient ultrasound loudspeakers, 36 and extreme UV protective membranes, 37 which makes the preliminary thickness assessment a difficult (or even impossible) task. Another approach proposed by Kuwahara et al 38 is based on thick film optical constants applied as a reference for thin films.…”
mentioning
confidence: 99%
“…The high optical contrast that we achieved using the pristine SWCNT membrane, is due to both the low diffuse and suppressed specular reflectance. A simple model of a scalar complex local dielectric permittivity can be applied for the theoretical description of specular reflectance (Rs) and transmittance (T) of the densified SWCNT membrane in the wavelength range from near UV to infrared [42]. We have calculated Rs and T using dispersion relation of refractive index and extinction coefficient, determined from the ellipsometry data, by means of Fresnel equations (for additional details, see Supporting Information, Section 6).…”
Section: Resultsmentioning
confidence: 99%
“…Single-walled carbon nanotubes (SWNTs) and fullerenes are well-known nanoscale materials with plasmonic activity within the near and mid-infrared and ultraviolet regions, respectively. Simulation of the electronic absorption spectra of large carbon nanotubes and fullerenes is computationally very costly, so that we have employed in this work the pseudo-π approach to investigate the electronic excitation modes involving the π-electron system in the SWNTs and fullerenes listed in Table .…”
Section: Results and Discussionmentioning
confidence: 99%